2016
DOI: 10.18632/oncotarget.9119
|View full text |Cite
|
Sign up to set email alerts
|

AT101 exerts a synergetic efficacy in gastric cancer patients with 5-FU based treatment through promoting apoptosis and autophagy

Abstract: Gastric cancer remains a disease with a high mortality rate despite of multiple therapeutic strategies. So far, it is very important to develop new treatment approaches to improve current therapeutic efficacy in gastric cancer. Apurinic/apyrimidinic endonuclease (APE1) involves in DNA base excision repair (BER) during DNA damage pathway. APE1 was found to be associated with poor overall survival with gastric cancer patients. In the in vitro experiment, we tested APE1 inhibitor-AT101 could potently inhibit gast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 24 publications
1
23
0
Order By: Relevance
“…Peripheral blood examination of APE1 enable to assist lymph node metastases assessment other than imaging evaluation. Our previous study indicated that APE1 inhibitor has synergetic effect to promote 5-FU based therapy in gastric cancer 3. We also search out the TCGA dateset to confirm our findings.…”
Section: Discussionsupporting
confidence: 70%
See 3 more Smart Citations
“…Peripheral blood examination of APE1 enable to assist lymph node metastases assessment other than imaging evaluation. Our previous study indicated that APE1 inhibitor has synergetic effect to promote 5-FU based therapy in gastric cancer 3. We also search out the TCGA dateset to confirm our findings.…”
Section: Discussionsupporting
confidence: 70%
“…Our study found that APE1 protein overexpression is associated with poor overall survival of gastric cancer patients 3. In this study, based on our previous results, we aim to explore the relationship between serum APE1 expression and gastric cancer lymph nodes involvement 3. We investigate the role of serum APE1 in further prediction of gastric cancer metastasis and prognosis.…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations
“…An APE1 inhibitor, AT101, was used to enhance 5-Fu treatment in non-small cell lung cancer in one study 20 . APE1 expression regulation has been shown to be involved in treatment of various cancers 5 , 6 , 20 , 21 . APE1 down-regulation increased chemotherapeutic sensitivity of cancer cells 20 , 21 .…”
Section: Discussionmentioning
confidence: 99%